Das mitologias clássicas às mitologias pop a performance como linguagem nas imagens de David Lachapelle - Molina, Márcia Morais (Universidade do Vale do Rio dos Sinos, 2013)
Understanding the context of the image and reflect on their possible interpretations have been an ongoing search in the media area. This work seek s to comprehend the relationship between photography and other fields of knowledge. Besides, we propose to discuss and reflect on this scenario, going through the various movements that contributed to the legitimization of contemporary photography. Under the influence of performance studies, photography and acting together assumed an important role in the process of signification imagery. For this reason, photography is the place of its event and i s thought as part of the actions and contributes to build an audience. We will study the work of David LaChapelle, surrealist photographer, we consider to be currently the largest heir of a line of photographers and artists that supported the visual arts of the twentieth century. The aim of this dissertation is to analyze how LaChapelle redefines a proposal in terms of performance. What is behind these images is undoubtedly a challenge, mainly methodological. For this reason, the importance of knowing the creative process and the photographic techniques employed by LaChapelle helps us to understand the elements used in his photographs. Among the main elements identified, our observation will focus on the theme, editing techniques, the ultra-saturated colors and the poses of his characters. These elements are active in a performative dimension, which is bounded to a better understanding, in theatrical, audiovisual and chromatic.
Keywords: Fotografia; Arte contemporânea; Comunicação social; Performance; David LaChapelle; Photography; Contemporary art. media; ACCNPQ::Ciências Sociais Aplicadas::Comunicação